CORPORATE ENTREPRENEURSHIP, STRATEGIC MANAGEMENT, EXTERNAL ENVIRONMENT AND PERFORMANCE OF INSURANCE COMPANIES IN NAIROBI, KENYA - GATHUNGU, JAMES M.; NDUNGI, EVALYNE N. (IJRDO - Journal of Business Management, 2018)
This study sought to establish the effect of corporate entrepreneurship and strategic management on firm performance of insurance companies in Nairobi, Kenya.. The study used descriptive survey design. The respondents were senior executives and managers of all the 49 registered insurance firms in Nairobi. Data was analyzed using descriptive statistics and interpreted using frequencies, percentages and mean score. Results were presented in form of frequency tables. The results indicated that insurance companies use rewards to motivate, proactive and innovative employees. Insurance companies also use management support and organizational boundaries to set precise explanations of outcomes expected from organizational work and development of mechanisms for evaluating selecting and innovations within the organization. It is evident that new products have been the reason behind high organizational performance among insurance companies. The study concludes that insurance companies in Kenya through rewarding employees and offering them the necessary support, provide innovative products to the market which will then lead to higher firm performance. The study recommends that companies should leverage internal resources, especially the employees, to help them gain competitive advantage.